Impact of hypertension on long-term humoral and cellular response to SARS-CoV-2 infection - Chu, Chang; Schönbrunn, Anne; Klemm, Kristin; von Baehr, Volker; Krämer, Bernhard; Elitok, Saban; Hocher, Berthold (Frontiers in immunology, 2022)
It was shown that hypertension delays SARS CoV-2 viral clearance and exacerbates airway hyperinflammation in the respiratory tract. However, it is unknown whether hypertension determines the long-term cellular and humoral response to SARS Cov2. Health care workers (HCWs) after an outbreak of SARS Cov-2 infections were analyzed. Infected HCWs were not vaccinated before blood collection. 5-14 months (median 7 months) after detection of SARS CoV-2 infection, blood was taken to analyze humoral response (S1 IgG and SARS CoV-2 neutralizing antibodies) and cellular (T cell responses to SARS-CoV-2 with Lymphocyte Transformation Test). To identify clinical factors that determine the immune response, a multivariate regression analysis was done considering age, BMI, sex, diabetes, hypertension, smoking, COPD, asthma and time between PCR positivity and blood collection as confounding factors. Infected hypertensive HCWs more often needed to be hospitalized than non-hypertensive HCWs, but were less likely to develop anosmia and myalgia. The long-term humoral and cellular immune response was significantly strengthened in hypertensive versus normotensive infected HCWs. Multivariate regression analysis revealed that hypertension was independently associated with the humoral response to SARS CoV-2 infection. Multivariate regression analysis using same confounding factors for the humoral response showed a clear trend for an association with the cellular response to SARS CoV-2 infection as well. In conclusion, SARS CoV-2 infection strengthened immune response to SARS CoV-2 infection in hypertensive HCWs independent of other risk factors.
Gesehen am 18.09.2023